A tumor control probability model for anal squamous cell carcinoma. Issue 2 (August 2015) - Muirhead, Rebecca; Partridge, Mike; Hawkins, Maria A.
Abstract: Background and purpose: A recent update of the RTOG 9811, reported differing relapse rates for early and late anal squamous cell carcinoma following chemoradiotherapy (CRT). There may be a role for dose-individualization, however the dose–response relationship for anal cancer is not currently known. Intensity-modulated radiotherapy (IMRT) has been widely adopted with multiple series published. The aim is to fit a tumor control probability (TCP) model to the published IMRT data. Materials and methods: We performed a systematic review of PubMed and Embase databases to identify thirteen appropriate papers, including 625 patients. Predefined data fields were collected. A standard linear quadratic TCP model, which included repopulation, was fit by least squares minimization. Results: The fitted TCP curve demonstrated a dose–response relationship with α = 0.196 Gy –1 . The curve suggests: in early stage tumours, a dose reduction from 50 Gy to 45 Gy reduces 2 year local control from 98% to 95%; in late stage tumours, a dose escalation from 50 Gy to 55 Gy improves the 2 year local control rate from approximately 50% to 80%. Conclusions: The published data are broadly consistent with a linear quadratic dose–response model. Dose-individualization in anal cancer should be further investigated in the context of clinical trials.